Harry Potter and the philosopher's stone - Rowling, Joanne K. (Bloomsbury, 1997)
Harry Potter thinks he is an ordinary boy until he is rescued by an owl, taken to Hogwarts School of Witchcraft and Wizardry, learns to play Quidditch and does battle in a deadly duel. The Reason: HARRY POTTER IS A WIZARD!